Association of Angina Pectoris with Some Heavy Metals Hospital Based Study - Yousif, Araz Muhammad (Diyala Journal of Medicine, 2019)
Background: Trace elements are essential for life and their concentrations in serum vary with human ecology and different pathological conditions. Several studies have pointed out associations between various metals and cardiovascular disease. Objectives: To evaluate the effect of serum metals such as: nickel, cobalt, cadmium, lead and mercury in patients with angina pectoris and compared to healthy individuals. Materials and methods: The studied consist of 100 volunteers with age range 40-65 years, 50 healthy individuals compared with 50 patients with angina pectoris in order to investigate the following serum parameters: serum lead, nickel, cobalt, cadmium and mercury levels, and lipids profile test [total cholesterol, high density lipoprotein, low density lipoprotein and triglyceride. Results: Circulating levels of serum lead, nickel, cadmium (p<0.001), cobalt (p<0.05) and mercury (p<0.007) were significantly higher in patients with angina pectoris than in healthy controls, while high density lipoprotein was decreased (p<0.05) and triglyceride, total cholesterol and low density lipoprotein were increased significantly (p<0.05) in patients angina pectoris compared with normal control. Conclusion: In this study high levels of heavy metals (cadmium, lead, nickel, cobalt, and mercury) were detected, which may play role in the genesis of angina pectoris, and this may be due to the main sources of contamination (dependent on the metal) are industry, traffic, tobacco consumption, and agriculture/nutrition. While lipoprofile such as total cholesterol, triglyceride, high density lipoprotein, and low density lipoprotein which may play role in genesis of angina pectoris.